FORMULASI MEDIA PRODUKSI JAMUR TIRAM (Pleurotus ostreatus) DENGAN SUPLEMENTASI AMPAS SAGU - Sri Utami; Umrah umrah; I Nengah Suwastika (Biology Department, Mathematics and natural science, Tadulako University, 2020)
This study aims to know the basic media with sago pulp supplementation which can be formulated into a medium for producing white oyster mushrooms and also to know the comparison of the right media and supplements in the formulation to give maximum oyster mushrooms production. In this study using a comparison with sawdust substrate and sago pulp to see how effective the sago pulp substrate as a supplement media for the oyster mushroom production. the program used is experimental designed in Completely Randomized Design (CRD), consists of three replications so that twelve experiments were obtained. The treatment arrangement is M1: Base media without supplements (controls), M2: 90% base media + 10% sago pulp, M3: 80% basic media + 20% sago pulp, M4: base media 70% + sago pulp 30%. The observation parameters used in the study are mycelium growth, fruit body growth, biological efficiency and measurement of protein levels in the fruit body of the oyster mushroom. The results showed that the addition of sago pulp in the media of oyster mushroom production had no effect on the growth of oyster mushrooms. This can be seen from the media of production of M1 (without the addition of sago pulp) experiencing a higher growth rate of mycelium compared to other treatments. The addition of sago pulp has an effect on the levels of oyster mushroom protein. This can be seen from the protein content of oyster mushrooms in M2 production media which have high protein content. Normal levels of white oyster mushrooms in sawdust media range from 18% -20%. This is due to the mixing of wood powder as a production medium and 10% sago pulp as supplementation to produce more nutrient levels.